Analisis Kinerja Ekspor Subsektor Perkebunan Indonesia dan Pandemi Covid-19: Institut Pertanian Bogor - Wildan Nur Arrasyiid Sane Pratinda; Rahmi Harta (IPB University, 2021)
The Covid-19 pandemic has had a major impact on aspects of life, especially the economy. The majority of economic sectors contracted during the pandemic. However, during the pandemic, the plantation sub-sector was able to survive with positive performance. This can be seen from its contribution to GDP, especially exports of the plantation sub-sector which grew by 10.68 percent when compared to 2019. The purpose of this study is to analyze the factors that affect Indonesia's plantation sub-sector exports during the period 1990-2020 using the multiple regression method. . Furthermore, this study analyzes the export performance of the plantation sub-sector during the Covid-19 pandemic and its impact on output, income, and labor using Input-Output analysis. The results of the study indicate that the factors that affect Indonesia's plantation sub-sector exports are Indonesia's nominal GDP, export prices of plantation sub-sector commodities, plantation sub-sector productivity, and the rupiah exchange rate against the US dollar. Meanwhile, exports of the plantation sub-sector, especially during the Covid-19 pandemic. The results of the analysis indicate that improving the performance of the plantation sub-sector needs to be carried out to encourage increased productivity so that it can affect the increase in export performance of the plantation sub-sector.